Transferring the freshwater dinoflagellate Peridinium wisconsinense (Dinophyceae) to the family Thoracosphaeraceae, with the description of Fusiperidinium gen. nov. Issue 2 (23rd March 2018) - McCarthy, Francine M.G.; Gu, Haifeng; Mertens, Kenneth N.; Carbonell‐Moore, Consuelo; Krueger, Andrea M.; Takano, Yoshihito; Matsuoka, Kazumi
SUMMARY: Distinctive spindle‐shaped thecae first described by Samuel Eddy in 1930 and assigned to the genus Peridinium Ehrenberg are commonly reported from freshwater environments in eastern North America. We demonstrate that thecae incubated from cysts of Peridinium wisconsinense Eddy have six cingular plates and a protuberant apical pore complex characteristic of the family Thoracosphaeraceae Schiller 1930 emend. Tangen in Tangen et al . 1982. Small subunit ribosomal DNA (SSU rDNA) and internal transcribed spacer (ITS) sequences confirm the close genetic similarity with Chimonodinium lomnickii (Wołoszyńska) Craveiro, Calado, Daugbjerg, Gert Hansen & Moestrup and with species recently reassigned to the genus Apocalathium Craveiro, Daugbjerg, Moestrup & Calado that was inferred from previously published LSU rDNA analysis of cysts of P. wisconsinense . Despite sharing identical tabulation with the thoracosphaeracean genera Chimonodinium Craveiro, Calado, Daugbjerg, Gert Hansen & Moestrup and Apocalathium, substantial morphological differences in the morphology of both the thecate and cyst stages of P. wisconsinense led us to reassign this species to the genus Fusiperidinium gen. nov. The phylogenetic position of Fusiperidinium wisconsinense comb. nov., inferred from concatenated data of SSU and LSU sequences, suggests that it evolved from the brackish Scrippsiella lineage, independently of the transition that produced the family Peridiniaceae. Cysts described as Geiselodinium tyonekensis Engelhardt from nonmarine strata from Alaska are apparently identical to the resistant cysts produced by F. wisconsinense . The palynologically‐constrained late Middle Miocene age for the Tyonek Formation provides a minimum age of 11.6 Ma for the evolution of this lineage, coinciding with a rapid glacioeustatic decline in sea level. Our findings also call into question the inclusion of the family Thoracosphaeraceae within the order Peridiniales Haeckel.